Morphological Features of Bundleia spp. (Ciliophora: Entodiniomorphida: Buetschliidae) and Ontogenesis in Bundleia Cunha and Muniz 1928 - Gürelli, Gözde; Göçmen, Bayram (Galenos Yayinevi, 2015)
The aim of this study was to investigate the morphological features of 7 endocommensal ciliates, B. (s. str.) postciliata, B. (s. str.) piriformis, B. (s. str.) nana, B. (C.) elongata, B. (C.) triangularis, B. (F.) dolichosoma, and B. (F.) inflata belonging to the genus Bundleia, which exist in the hindgut of 15 Rahvan horses and 15 racing horses living in the vicinity of Izmir and to investigate the ontogenesis in the Bundleia genus.Specimens were obtained from 30 horses and were fixed with 10% formalin. The morphological features of the species were investigated with the pyridinated silver carbonate impregnation and silver nitrate impregnation techniques at the level of light microscopy.The morphological features of Bundleia spp. were found to be similar to the original descriptions, and it was detected that ontogenesis in the Bundleia genus exhibited suitability with other ciliate species in the Entodiniomorphida order.We conclude that the geographical variation and feeding habits of host animals are important for evaluating the biometric data of species.
Keywords: Silver Staining; Carbonates; Animals; Silver Compounds; Ciliophora Infections; Horse Diseases; Horses; Ciliophora; 2. Zero hunger